Community Voices in Sustainable Slum-Upgrading Processes: The Nairobi People Settlement Network - (:unkn) unknown (My University, 2011)
This article presents the slum upgrading activities of the Nairobi People Settlement Network (NPSN) beginning with an historical background of this movement. It focuses on the participation of the community in these processes through highlighting NPSN goals, achievements and challenges in contributing to sustainable slum-upgrading programmes.
Keywords: African Research